Effect of feeding ratio on the growth of common carp cultivated in earthen ponds - Taher, Majid M.; Muhammed, Sadiq J.; Salih, Osamah A.; Al-Dubakel, Adel Y.; Mojer, Ahmed M. (Iraqi Journal of Aquaculture, 2023)
The current experiment was conducted in earthen ponds at the Agricultural Research Station belonging to the Aquaculture Unit- Agriculture College at Basrah University, Al-Hartha District about 16 km northern-east of Basrah Governorate (30o39`20.264"N, 47o 44`51.533"E) from 25th July to 23rd October 2021. The feeding experiment begin after ten days of fish acclimation. Six small earthen ponds (600 m2) were used for the current experiment to investigate the differences in growth criteria for 200 individuals of common carp fed (2 T1, 3 T2 and 4 T3) % of total fish weight. Fishes were fed daily on commercial pellets manufactured by Agricultural Consultant Office belonging to Agriculture College. The total length and weight of fish were measured at the beginning and the end of the experiment, while subsamples of fish were weighed periodically and daily food changed after each weighing. Initial fish weights were 530.0± 132.7, 513.4±118.3 and 477.3±122.5 for T1, T2 and T3 respectively. Daily feed was divided into three meals, the first given early in the morning, the second at mid-day and the third given in the afternoon. Results of current experiments showed a high growth rate (FW= 1341.4 g, WI= 873.0 g, DGR=9.59 g/day and SGR=1.16 %/day) for fish fed on 4% feeding ratio compared with the two feeding ratios. Feed conversion rates were 2.46, 4.01 and 3.28 for T1, T2 and T3 respectively. Statistical analysis showed that there were no significant differences (P>0.05) between values of b with value 3 (Isometric pattern of growth) of common carp before and after the experiment. Statistical analysis of three models for condition factor proved that there were significant differences (P≤0.05) between the values before the experiment with values after the experiment, while there were no significant differences (P>0.05) after the experiment between different condition factors for common carp reared on different feeding ratio.